2011
DOI: 10.1080/02607476.2011.538274
|View full text |Cite
|
Sign up to set email alerts
|

Literacy metaphors of pre‐service teachers: do they change after instruction? Which metaphors are stable? How do they connect to theories?

Abstract: The purpose of this study was to examine pre-service elementary teachers' metaphors of "literacy" and "teaching literacy" at the commencement and conclusion of a year-long literacy methods course at a Midwestern American university. Over a 3-year period, a total of 47 participants enrolled in the twosemester literacy methods course with embedded practicum. Data were entered in NVivio 7 and analyzed for qualitative themes. Results identified six themes of teaching literacy, five of which connect to literacy the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 32 publications
1
16
0
7
Order By: Relevance
“…Some of the elements include writing strategies, summarizing, collaborating, goals, prewriting, sentence combining, and the process writing approach. Since the idea of parts or elements is fairly dominant in the research, it is no surprise that previous research (Massengill & Mahlios, 2008;Massengill Shaw & Mahlios, 2011) identified this as a prevailing metaphor. However, it is a surprise that adult students in need of literacy instruction identified this as a dominant metaphor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the elements include writing strategies, summarizing, collaborating, goals, prewriting, sentence combining, and the process writing approach. Since the idea of parts or elements is fairly dominant in the research, it is no surprise that previous research (Massengill & Mahlios, 2008;Massengill Shaw & Mahlios, 2011) identified this as a prevailing metaphor. However, it is a surprise that adult students in need of literacy instruction identified this as a dominant metaphor.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in metaphor selection have been found between pre-service and in-service teacher beliefs (Martinez, Sauleda, & Huber, 2001), male and female teachers (Saban, Kocbeker, & Saban, 2007), and content area teachers (Saban, Kocbeker, & Saban, 2007). Research on literacy metaphors of pre-service elementary teachers have identified six themes of teaching literacy, five of which connect to literacy theories (Massengill Shaw & Mahlios, 2011). Themes of teaching that arose in previous research, specifically nurturing and guiding (Mahlios & Maxson, 1998), were evident in the literacy metaphor responses of the population in the more recent study as well, illustrating their commonality and perhaps widespread nature.…”
Section: International Journal Of Research Studies In Education 23mentioning
confidence: 99%
“…Features attributed from the source of metaphor to the subject of metaphor (The word "precious" in the statement, "FMs are like boron mine because they are precious.") This question which was prepared examining the studies by Erickson and Pinnegar (2017), Ma and Gao (2017), Shaw and Mahlios (2011), Vickery (2018), was presented to two field experts for their opinions. The question was arranged according to the opinions of the field experts.…”
Section: Development and Application Of Data Collection Toolmentioning
confidence: 99%
“…Respecto a la metodología, creen que la lectura debe enseñarse en forma lineal, yendo de lo simple a lo complejo (fonemas, decodificación y vocabulario); y la escritura consistiría en deletrear, poner mayúsculas, signos de puntuación y usar frases completas; además, esto ocurriría naturalmente después de aprender a leer (Añorve, 2011;Shaw y Mahlios, 2011;Stevens y Palincsar, 1992).…”
Section: Marco Teóricounclassified